2012
DOI: 10.1055/s-0032-1323819
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Resistance Exercise on 24-h Blood Pressure in Middle Aged Overweight and Obese Women

Abstract: This investigation was designed to evaluate responses of blood pressure (BP) following an acute resistance exercise (RE) session. Middle-aged women (N=13) who were classified as overweight (N=8) or obese (N=5) according to body mass index (BMI) participated in the investigation. Participants were randomly submitted to a control session (30-min seated rest) and a exercise session (3 sets, 10 repetitions at 60% 1RM of exercises for the upper and lower body) with systolic (SBP), diastolic (DBP) and mean blood pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 27 publications
6
34
1
3
Order By: Relevance
“…The magnitude of these changes in BP are within the range of values that has been observed in younger and middle-aged normotensive healthy subjects (Queiroz et al 2009(Queiroz et al , 2013(Queiroz et al , 2014 and slightly lower (especially for DBP) than that observed in normotensive/pre-hypertensive overweight and obese middle-aged women (−7 mmHg for SBP and −6 mmHg for DBP) (Tibana et al 2013). It is not clear why a lower magnitude of post-exercise hypotension was observed when compared with Tibana and colleagues' investigation (Tibana et al 2013). A possible explanation could be related with nutritional status of the participants included in these two studies, given that the exercise protocol adopted in both studies was very similar.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The magnitude of these changes in BP are within the range of values that has been observed in younger and middle-aged normotensive healthy subjects (Queiroz et al 2009(Queiroz et al , 2013(Queiroz et al , 2014 and slightly lower (especially for DBP) than that observed in normotensive/pre-hypertensive overweight and obese middle-aged women (−7 mmHg for SBP and −6 mmHg for DBP) (Tibana et al 2013). It is not clear why a lower magnitude of post-exercise hypotension was observed when compared with Tibana and colleagues' investigation (Tibana et al 2013). A possible explanation could be related with nutritional status of the participants included in these two studies, given that the exercise protocol adopted in both studies was very similar.…”
Section: Discussionsupporting
confidence: 72%
“…A possible explanation could be related with nutritional status of the participants included in these two studies, given that the exercise protocol adopted in both studies was very similar. In our study, the majority of women had normal weight or slightly overweight, while only overweight or obese women were included in Tibana and colleagues' study (Tibana et al 2013). Probably, endocrine, neural, autonomic, and cardiac alterations Fig.…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies have shown that both exercise modes promoted BP reduction in both healthy individuals and patients with hypertension and metabolic syndrome. For example, Tibanaet al 18 conducted a study with RE (3 series of 10 repetitions with 60% of 1MR in 6 exercises) in overweight and obese women and analyzed clinical and ambulatory BP (over 24h). Similarly, after a RE session, SBP decreased at times 10, 30 and 40 minutes and DBP after 10 and 40 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…BP reduction after an acute exercise session has been associated with chronic reduction of resting BP 11,12 . These BP reductions after exercise were demonstrated in hypertensive individuals 13,14 , individuals with SM 15 , normotensive individuals 16,17 and after aerobic exercises 13,17 and inresistanceexercise (RE) 15,17,18 . In fact, more recently, some studies have found that PEH also occurs after the combination of aerobic (AE)and strength exercise.…”
Section: Introductionmentioning
confidence: 90%
“…Número de repetições: Foi realizada através de zona de repetição priorizando hipertrofia muscular, (8)(9)(10)(11)(12).…”
Section: Protocolo Do Treinamento Resistidounclassified